Traveling Thrombus in the Right Atrium: Is It the Final Destination? - Maneesh Bhargava; Erhan Dincer (Case Reports in Pulmonology)
Right heart thrombus is rare in structurally normal heart. Here, we report a 74-year-old man with a right atrial thrombus who presented with shortness of breath.